Sustainable Ship Manning Performance in Indonesia - Gatot Cahyo Sudewo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the study is to describe and provide explanations for variables written using a literature review of various scientific articles related to this scientific article. The results of the research of the recruitment system with significant work performance, occupational safety to the performance of the crew are significant there is a mediation of motivational variables, the importance of maritime English for sailors, knowledge of sailing safety, as well as, the health of the crew has a positive impact on the performance of the crew during sailing. Recommendations for the future with the limitations of current researchers in seeking literature review, the results of this study can add to the characteristics and knowledge in the field of marine transportation in general.